The cost of inaction in air pollution abatement policies. Issue 5 (2022) - Arrighini, Michele; Guariso, Giorgio; Volta, Marialuisa; Zecchi, Laura
Abstract: Two alternative air quality policies are compared: one is the application of only mandatory abatement measures from 2020 to 2030. The second is the definition of a more active and locally-based policy that will lead to a better air quality at the end of the decade. Using an integrated modelling system, we demonstrate that the active policy is quite more convenient from the economic viewpoint, at least for the specific situation of the Lombardy region, considered in the study. Improving particulate matter concentrations may however produce worse ozone values. A full view of all pollutants is thus necessary when planning for air quality at regional level.